2020
DOI: 10.1155/2020/5795264
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Features and Rules of Chinese Herbal Medicine in Diabetic Peripheral Neuropathy Patients

Abstract: Objective. To analyse the clinical features of diabetic peripheral neuropathy (DPN) and employ data mining technology to explore the rules of Chinese herbal medicine (CHM) therapy. Methods. The clinical data of 216 patients with DPN and qi-yin deficiency syndrome were obtained, and the clinical features of the patients were assessed by cluster analysis. Relevant information was entered into the clinical diagnosis and treatment collection system, and data mining techniques were used to analyse the drug frequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 49 publications
1
8
0
Order By: Relevance
“…The evidence related to the use of EAHM therapy for PN supported by this study is consistent with the results of previous studies on similar subjects. A study analyzing the clinical data for DPN after using 216 EAHM prescriptions found that the combination of Astragali Radix-Cinnamomi Ramulus and Ligusticum Chuanxiong-Moutan Radicis Cortex highly correlated with MDNS improvement [105]. Moreover, considering that Astragali Radix and Cinnamoni Ramulus are among the top 10 herbs utilized and their combination was identified as a core herb pattern, the findings of the previous study are similar to this study.…”
Section: Implications Of Clinical Practicessupporting
confidence: 84%
“…The evidence related to the use of EAHM therapy for PN supported by this study is consistent with the results of previous studies on similar subjects. A study analyzing the clinical data for DPN after using 216 EAHM prescriptions found that the combination of Astragali Radix-Cinnamomi Ramulus and Ligusticum Chuanxiong-Moutan Radicis Cortex highly correlated with MDNS improvement [105]. Moreover, considering that Astragali Radix and Cinnamoni Ramulus are among the top 10 herbs utilized and their combination was identified as a core herb pattern, the findings of the previous study are similar to this study.…”
Section: Implications Of Clinical Practicessupporting
confidence: 84%
“…We demonstrated that gut microbiota is a pharmacological target to exert a hypoglycaemic effect after berberine treatment of T2DM rats, but the mechanism is not yet entirely clear. Gut microbiota may also have a potential signalling function that needs to be studied for wider clinical and experimental usage[ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent findings have indicated its role in modulating glucose metabolism and controlling progression of diabetes. Astragalus Radix is a common Chinese medicine used to treat diabetes [26], and a report has demonstrated that Astragalus Radix can regulate blood lipid and blood glucose levels in HFD-fed mice [27]. Previously, we found active Evidence-Based Complementary and Alternative Medicine flavonoid components of Astragalus Radix have protective effects against diabetic damage in vitro [10][11][12][13], but its influence on bile acid metabolism was not studied.…”
Section: Discussionmentioning
confidence: 99%